Pertimbangan Hukum Dalam Putusan Rehabilitasi Terhadap Pelaku Tindak Pidana Narkotika Sesuai Dengan SEMA No. 4 Tahun 2010 (Studi Putusan Pengadilan Negeri Tanjung Pinang No. 267/Pid.Sus/2018/PN.Tpg Dan Putusan Pengadilan Negeri Tanjung Pinang No. 233/Pid.Sus/2018/PN.Tpg) - Jhon Leonardo Hutagalung; Madiasa Ablisar; Mahmud Mulyadi; M Ekaputra (Iuris Studia: Jurnal Kajian Hukum, 2022)
Tanjung Pinang District Court No. 267/Pid.Sus/2018/PN.Tpg ignores the elements of narcotics abuse specifically the minimum amount listed in Article 127 of Law No. 35 of 2009 concerning Narcotics and SEMA No. 4 of 2010 concerning the Determination of Abuse and Narcotics Addicts into the Institute of Medical Rehabilitation and Social Rehabilitation with imprisonment. However, this is inversely proportional to other Tanjungpinang court decisions, namely decision No. 233/Pid.Sus/2018/PN.Tpg who handed down the rehabilitation decision to the convicted person